Yahoo Web Search

  1. Sort by

  1. ...5x/4 -1 = 3x - 4x/6 +9 then shifting -1 to RHS and 3x - 4x/6 to LHS, we get 2x - 5x/4 - 3x + 4x/6 = 9+1 Multiply both side by 12 24x - 15x...

    3 Answers · Science & Mathematics · 21/10/2010

  2. ...u+1)/u u du/(u+1) = dx Now it's separated; to integrate the LHS, let v=u+1, so (1 - 1/v) dv = dx v - ln|v| = x + C1 u - ln|u+1| = x + ...

    2 Answers · Science & Mathematics · 02/10/2013

  3. ...all n from 1 to ∞ (note zero is not a positive integer) 2. For n=1, LHS = (a+b) and RHS = a+b so the formula holds and P(n=0) ...

    1 Answers · Science & Mathematics · 27/03/2011

  4. ...c. The system is stable.All roots are on the LHS of the real axis!!

    2 Answers · Science & Mathematics · 21/04/2011

  5. ...)/ (x^2+1)^2 Then multiply all terms by the denominator of the LHS, and equate coefficients for each separate power of x. I admit this...

    2 Answers · Science & Mathematics · 23/12/2013

  6. ...st) ] dt ADD the integral from the RHS to the original integral on the LHS, obtaining: [1 + (a^2/s^2)] * F(s) = 1/s + [(a/s^2)*(sin at)*e^(-st...

    3 Answers · Science & Mathematics · 11/08/2014

  7. ...or particular solution of the complete (non-homogeneous) equation. Try y=sinx , then the LHS: y" + 4y = -sinx +4.sinx = 3sinx so the solution fits! giving the general...

    3 Answers · Science & Mathematics · 29/12/2012

  8. ...x) - cos(x)/sin(x) = tan(x) - cot(x) But now it's perfectly clear that the LHS equals the RHS.

    1 Answers · Science & Mathematics · 23/04/2013

  9. ...gal )( 10 gal/min ) dQ/dt = -10Q / 55 Move Q to the LHS and then integrate ∫ 1/Q dQ = -10/55 ∫ dt ln Q = -10t/55...

    2 Answers · Science & Mathematics · 11/12/2009

  10. ...since, 1+any = 1: 1+C =1, 1+B=1 } =AB+A'C = LHS

    2 Answers · Science & Mathematics · 27/09/2012

  1. Ads
    related to LHS
  1. Try asking your question on Yahoo Answers